Prognosis Evaluation Using 18F-Alfatide II PET in a Rat Model of Spinal Cord Injury Treated With Estrogen. (2nd March 2020) - Tan, Hongpei; Tang, Yongxiang; Li, Jian; He, Tingting; Zhou, Ming; Hu, Shuo
Spinal cord injury (SCI) leads to severe dysfunction below injured segment and poses a great pressure to the individual and society. In this study, we applied 18 F-alfatide II positron emission tomography/computed tomography (PET/CT) to monitor angiogenesis in an SCI model after estrogen (E2) treatment, as well as to evaluate the prognosis in a noninvasive manner. The SCI model was established with male rats and the rats were randomly divided into E2-treated group (SCI + E2) and E2-untreated group (SCI). Sham group was also used as control (Sham). The angiogenesis after SCI was monitored by 18 F-alfatide II PET/CT and verified by immunofluorescence of CD31 and CD61. We also evaluated the level of E2 and growth-associated protein 43 (GAP43) by enzyme-linked immunosorbent assay. Finally, Basso, Beattie, and Bresnahan (BBB) scores were determined to evaluate the exercise capacity of the rats in all 3 groups. Our results showed that the BBB score of SCI + E2 group was significantly different from that of SCI group ( P < .05) and Sham group ( P < .01). The uptake of 18 F-alfatide II was positively correlated with the expression level of GAP43, both of which reached the peak at day 7 after injury. CD31 and CD61 immunostaining further verified increased angiogenesis in E2-treated SCI lesions. We concluded that 18 F-alfatide II PET/CT can monitor the angiogenesis status after SCI in vivo and it may help clinician predict the progression of patients with SCI. This may benefit the study of vascular repair after SCI and provide a tool for evaluation of SCI treatment in clinical practices.